Assessing Patient Radiation Exposure in Endoscopic Retrograde Cholangiopancreatography: A Multicenter Retrospective Analysis of Procedural Complexity and Clinical Factors - Kaasalainen, Touko; Saukko, Ekaterina; Lindström, Outi; Udd, Marianne; Regnér, Sara; Saarela, Arto; Toth, Ervin; Wurm Johansson, Gabriele; Manninen, Anna-Leena; Grönroos, Juha; Kylänpää, Leena (MPDI, 2025)
Background and aims: Endoscopic retrograde cholangiopancreatography (ERCP) procedures can result in significant patient radiation exposure. This retrospective multicenter study aimed to assess the influence of procedural complexity and other clinical factors on radiation exposure in ERCP.
Methods: Data on kerma-area product (KAP), air-kerma at the reference point (Ka,r), fluoroscopy time, and the number of exposures, and relevant patient, procedure, and operator factors were collected from 2641 ERCP procedures performed at four university hospitals. The influence of procedural complexity, assessed using the American Society for Gastrointestinal Endoscopy (ASGE) and HOUSE complexity grading scales, on radiation exposure quantities was analyzed within each center. The procedures were categorized into two groups based on ERCP indications: primary sclerosing cholangitis (PSC) and other ERCPs.
Results: Both the ASGE and HOUSE complexity grading scales had a significant impact on radiation exposure quantities. Remarkably, there was up to a 50-fold difference in dose quantities observed across the participating centers. For non-PSC ERCP procedures, the median KAP ranged from 0.9 to 64.4 Gy·cm2 among the centers. The individual endoscopist also had a substantial influence on radiation dose.
Conclusions: Procedural complexity grading in ERCP significantly affects radiation exposure. Higher procedural complexity is typically associated with increased patient radiation dose. The ASGE complexity grading scale demonstrated greater sensitivity to changes in radiation exposure compared to the HOUSE grading scale. Additionally, significant variations in dose indices, fluoroscopy times, and number of exposures were observed across the participating centers.